GAMBARAN FUNGSI PARU DAN KELUHAN MUSKULOSKELETAL PADA PEKERJA PENGISIAN LPG (LIQUIFIED PETROLEUM GAS) DI DENPASAR - I Gusti Ngurah Nugraha Agung; Luh Made Indah Sri Handari Adiputra (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2016)
LPG filler workers are the individuals that susceptible to having a lung function abnormality and musculoskeletal disorders due to their type of work. If those problems happen, it could affect productivity and quality of life of the workers. The purpose of this research is to determine the description of lung function and musculoskeletal disorders on LPG filler workers in Denpasar. This research was using a cross-sectional study involved 45 people as the subjects. In this research, the subjects are tested their lung function using spirometer and filled a Nordic Body Map questionnaire. The spirometry test showed 23 people (51%) are having lung function abnormality as follows: 17 subjects (38%) with restrictive lung, 4 subjects (9%) with obstructive lung, and 2 subjects  (4%) with mixed lung abnormality. Musculoskeletal disorders are mostly experienced on waist 35 subjects (78%), left knee 22 subjects (48%), back 22 subjects (48%), upper neck 21 subjects (47%), and lower neck 21 subjects (47%). Those problems might be associated with working position and work posture during filling the LPG. The characteristic of lung function on LPG filler workers was found mostly restrictive lung function. In the musculoskeletal disorders, the prevalence is mostly on the waist, left knee, and on the back.